An Investigation of the Pre-Service Teachers’ Emotional Awareness in China - Chen Y; Feng Z; Wang H (Psychology Research and Behavior Management)
Yezi Chen,1 Zhouqi Feng,1 Haibin Wang2 1School of Urban Governance and Public Affairs, Suzhou City University, Suzhou, Jiangsu, People’s Republic of China; 2School of Educational Science, Huangshan University, Huangshan, Anhui, People’s Republic of ChinaCorrespondence: Haibin Wang, School of Educational Science, Huangshan University, Huangshan, Anhui, People’s Republic of China, Tel +86 13855910608, Email asdwhb@163.comPurpose: Emotional awareness, fundamental to emotional intelligence, involves recognizing and describing emotions in oneself and others, critically influencing mental health and relationships. Therefore, this study aimed to analyze the emotional awareness of pre-service teachers in Chinese through the revised emotional awareness scale (LEAS).Participants and Methods: The two-stage study included 455 pre-service teachers for LEAS revision (Study 1) and 773 pre-service teachers (randomly sampled) alongside in-service teachers as a contrast group (Study 2).Results: The revised LEAS showed a strong reliability (total α = 0.888; self/others-awareness α = 0.860/0.822) and validity, with self/others-awareness subscales highly correlated (r = 0.797) and strongly linked to total scores (r = 0.937/0.925). In addition, the criterion-related validity test found that the LEAS was significantly and positively correlated with the TMMS and QYEI. Pre-service teachers’ mean emotional awareness score (2.730) was below the theoretical midpoint (3). Females scored higher than males, awareness increased with academic grade, and liberal arts students outperformed science peers. In-service teachers had higher self/others-awareness than pre-service groups, but total scores of senior pre-service teachers matched in-service levels.Conclusion: The revised LEAS exhibited good reliability and validity and could be used as an effective tool to measure emotional awareness. Pre-service teachers’ emotional awareness ability, in general, is low to medium and needs improvement. Pre-service teachers’ emotional awareness differed significantly by gender, grade, and profession. The cultivation of emotional awareness is very important and necessary for teachers and is more important for pre-service teachers.Keywords: pre-service teacher, emotional awareness, LEAS, investigation, China